Development and analysis of a SmPC-based machine-readable dataset of contraindications for clinical decision support and real-world data analysis - Miriam Schechner; Wahram Andrikyan; Thomas Bauerdick; Theresa Terstegen; Louisa Redeker; Martin Federbusch; Katrin Farker; Alexander Strübing; Florian Schmidt; Petra Thürmann; Sven Schmiedl; Hanna M. Seidling; et al. (European Journal of Clinical Pharmacology, 2026)
Purpose Unrecognized contraindications pose risks for adverse drug reactions, hospitalizations or death. Clinical decision support systems (CDSS) aim to mitigate medication-related harm, particularly originating from contraindications. However, many CDSS provide limited benefit, as they focus largely on singular risk situations such as drug-drug interactions and often generate alerts of limited clinical relevance. Comprehensive integration of contraindications into CDSS may support more clinically meaningful alerts. The aim of this work was the development and analysis of machine-readable contraindication lists, including drug-clinical condition, drug-kidney function and drug-drug (group) contraindications, for integration into CDSS and real-world data analysis. Methods We extracted and operationalized contraindications, based on Summaries of Product Characteristics (SmPCs), of the 688 most prescribed drugs in Germany, leveraging common medical coding systems. Moreover, we analyzed extracted contraindications based on operationalizability, overall frequency and frequencies within different contraindication categories. Results In total, we extracted 4676 contraindications, of which 2129 (45.5%) were deemed operationalizable. Of these 2129 contraindications, 1652 (77.6%) were attributed to drug-clinical condition, 83 (3.9%) to drug-kidney, 140 (6.6%) to drug-drug group and 254 (11.9%) to drug-drug. The most frequently mentioned contraindicated risk situations were ‘severe liver insufficiency’ ( n = 74, 3.5%), ‘pregnancy’ ( n = 66, 3.1%), ‘MAO-inhibitors’ ( n = 44, 2.1%), and ‘shock’ ( n = 44, 2.1%). Conclusion Our results show, that drug-clinical condition contraindications are listed far more frequently in SmPCs than other contraindication categories. Focusing on clinical condition-related contraindications within CDSS could improve the detection of clinically relevant contraindications in routine data and enhance medication safety. The clinical applicability is currently being evaluated in the INTERPOLAR study.

Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Bundesweite Entwicklung der Grundwasserstände seit 1991: Langzeittrends, Variabilität und Auswirkungen der jüngsten Trockenphase - Maria Wetzel; Stefan Broda; Mariana Gomez; Markus Zaepke; Patrick Clos; Stefan Kunz; Tanja Liesch; Marc Ohmer; Bastian Habbel; Michel Wingering; Bernhard Pitschka; Antje Roucka; et al. (Grundwasser, 2026)
Zusammenfassung Die Studie untersucht die Entwicklung der Grundwasserstände in Deutschland anhand von 5844 Messstellen sowie deren Reaktionsdynamik gegenüber klimatologischen Antrieben im Referenzzeitraum 1991–2020. Zusätzlich wird die Entwicklung seit 2018 im Kontext der außergewöhnlichen Dürreperiode betrachtet, um die Reaktionsfähigkeit und Vulnerabilität der Grundwassersysteme gegenüber extremen klimatischen Bedingungen zu bewerten. Erstmals erfolgt diese Auswertung bundesweit einheitlich und in enger Zusammenarbeit mit den zuständigen Landesbehörden. An 43 % der untersuchten Messstellen werden signifikante Trends festgestellt, überwiegend in Form fallender Grundwasserstände mit einem Medianrückgang von 0,9 cm pro Jahr. Dies entspricht einem jährlichen Rückgang von 0,5 %, bezogen auf die Spannweite der jeweiligen Grundwasserganglinie. Diese Entwicklungen sind deutschlandweit erkennbar, jedoch regional unterschiedlich ausgeprägt und überwiegend klimatisch bedingt. Um Unterschiede in der Reaktionsdynamik systematisch zu erfassen, werden die Messstellen anhand ihrer Autokorrelationslängen in vier Dynamikklassen eingeteilt. Mit abnehmender Dynamik zeigt sich für den Referenzzeitraum eine Zunahme langfristiger Trends (von −0,3 % pro Jahr in Dynamikklasse 1 bis −1,16 % pro Jahr in Klasse 4) sowie eine höhere Persistenz klimatischer Effekte. Träge Systeme reagieren verzögert und sind damit nachhaltiger von Niedrigständen betroffen (Median: 9,8 Monate), während schnell reagierende Systeme kürzere Niedrigstandsphasen (Median: 2,2 Monate) aufweisen und sich rascher erholen. Besonders in der Entwicklung seit 2018 werden diese Unterschiede deutlich: Rund 60 % der trägen Messstellen weisen über fünf Jahre hinweg anhaltend niedrige Grundwasserstände auf, wobei etwa 20 % neue Niedrigstände erreichen und damit unterhalb der Minimalwerte der Referenzperiode liegen. Die Ergebnisse verdeutlichen den engen Zusammenhang zwischen klimatischer Variabilität und Grundwasserdynamik und bilden eine Grundlage für die fortlaufende Bewertung der Grundwasserstandsentwicklung in Deutschland.

Linked cell traversal algorithms for three-Body interactions in molecular dynamics - José Alfonso Pinzón Escobar; Markus Mühlhäußer; Hans-Joachim Bungartz; Philipp Neumann (Computer Physics Communications, 2026)

Prescribed burning as a potential regeneration technique for reed stands: a pilot study in the reed belt of Lake Neusiedl, Austria - Raffael Berner; Mathias Neumann; Mortimer Müller; Markus Hollaus; Andreas Maier; Thomas Zechmeister; Stephan Glatzel (Wetlands Ecology and Management, 2025)
Nature conservation calls for the management of reed in large stands to support the rejuvenation of reed. Traditional reed management tools at Lake Neusiedl are becoming decreasingly suitable due to insufficient freezing in winter. Therefore, prescribed burning of old Phragmites australis stands is currently being considered as a regeneration measure to promote reed regrowth and maintain invaluable habitats for specialized species in the reed belt. In January 2024 a pilot study was carried out near the municipality of Jois to gain insights into suitability and consequences of controlled burning of old reed mats in the reed belt. Applied methods include pre- and post-fire biomass and carbon content analyses from vegetation, litter and soil, fire behavior and intensity monitoring, moisture content measurements during and after the fire, and area-wide UAV-LiDAR mapping. Mean fire temperature was approx. 700 °C and peaked at 1034 °C. 15.57 ha of the 32 ha study area were affected by the fire, and a total of 57.84 tons of carbon were released (3.72 t C/ha). On burnt areas standing vegetation was removed and litter thickness significantly reduced by approx. 30%, while no biomass loss from soil was detected. Fuel moisture content is negatively correlated to distance from the water table and has mitigating effects on fire spread if above 30%, resulting in unaffected deeper layers and numerous unburnt refugia patches within the fire perimeter. Our results indicate that prescribed fire can be a suitable management tool at Lake Neusiedl for the purpose of reed rejuvenation and wetland habitat regeneration.

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Warm saltwater inflows strengthen oxygen depletion in the western Baltic Sea - Leonie Barghorn; H. E. Markus Meier; Hagen Radtke; Thomas Neumann; Lev Naumov (Climate Dynamics, 2025)
Hypoxia is a major environmental threat for coastal seas, including the strongly-stratified Baltic Sea in northern Europe. There, a pronounced increase in nutrient loads since the 1950s led to the development of one of the largest hypoxic areas worldwide. So far, other drives of hypoxia, like the increase in water temperatures due to global warming, have been considered minor compared to eutrophication. We show, by analyzing 159-years long hindcast simulations of three different Baltic Sea models, that exceptional warming trends in deep water layers of the western Baltic Sea deteriorated the local oxygen conditions. The above-average warming is only to a small extent attributed directly to global warming, but mainly to a shift in the seasonality of saltwater inflows from the North Sea towards more warm summer and early autumn inflows. Hence, we identify a so far unknown driver of oxygen depletion in the western Baltic Sea with potentially serious ecological consequences.

Carbapenemase-producing Gram-negative bacteria in hospital wastewater, wastewater treatment plants and surface waters in a metropolitan area in Germany, 2020 - Markus Hoffmann; Martin A. Fischer; Bernd Neumann; Katja Kiesewetter; Ines Hoffmann; Guido Werner; Yvonne Pfeifer; Christoph Lübbert (Science of The Total Environment, 2023)

Dynamics of oxygen sources and sinks in the Baltic Sea under different nutrient inputs - Lev Naumov; H. E. Markus Meier; Thomas Neumann (Frontiers in Marine Science, 2023)
The Baltic Sea is one of the marine systems suffering from pronounced man-made hypoxia due to the elevated nutrient loads from land. To mitigate hypoxia expansion and to return the Baltic Sea to a good environmental state, the Baltic Sea Action Plan (BSAP), regulating the waterborne and airborne nutrient input, was adopted by all states surrounding the Baltic Sea. However, at the moment, no significant shrinking of the hypoxic area is observed. In this study, two scenario simulations of the future state of the deep parts of the central Baltic Sea (deeper than 70 meters) were carried out, utilizing a 3-dimensional numerical model. Climate change effects on meteorology, hydrology, and oceanic state were not included. We focused on O 2 and H 2 S sources and sinks under different nutrient input scenarios. We found that under the BSAP scenario, all subbasins in the central Baltic Sea, especially the northern and western Gotland Basin, show significant improvement, namely, oxygenation and oxidation of the deposited reduced material, ceasing its advection to the upper layers and neighboring basins. We found that the nutrient loads are responsible for more than 60% and 80% of the O 2 and H 2 S sources and sinks variability, respectively, at the interannual time scale. We showed that the Baltic Sea could return to the initial state in 1948, but under the more rigorous 0.5 BSAP scenario (nutrient input is halved compared to the BSAP). However, since we observed no hysteresis effect, the system would probably reach the initial state but over a timeframe longer than the 71-year future simulation period.

Deoxygenation of the Baltic Sea during the last millennium - Florian Börgel; Thomas Neumann; Jurjen Rooze; Hagen Radtke; Leonie Barghorn; H. E. Markus Meier (Frontiers in Marine Science, 2023)
Over the last 1,000 years, changing climate strongly influenced the ecosystem of coastal oceans such as the Baltic Sea. Sedimentary records revealed that changing temperatures could be linked to changing oxygen levels, spreading anoxic, oxygen-free areas in the Baltic Sea. However, the attribution of changing oxygen levels remains to be challenging. This work simulates a preindustrial period of 850 years, covering the Medieval Climate Anomaly (MCA) and the Little Ice Age using a coupled physical-biogeochemical model. We conduct a set of sensitivity studies that allow us to disentangle the contributions of different biogeochemical processes to increasing hypoxia during the last millennium. We find that the temperature-dependent mineralization rate is a key process contributing to hypoxia formation during the MCA. Faster mineralization enhances the vertical phosphorus flux leading to higher primary production. Our results question the hypothesis that increased cyanobacteria blooms are the reason for increased hypoxia in the Baltic Sea during the MCA. Moreover, the strong contribution of the mineralization rate suggests that the role of temperature-dependent mineralization in current projections should be revisited.

Limited ventilation of the central Baltic Sea due to elevated oxygen consumption - Lev Naumov; Thomas Neumann; Hagen Radtke; H. E. Markus Meier (Frontiers in Marine Science, 2023)
The Baltic Sea is known as the world’s largest marine system suffering from accelerating, man-made hypoxia. Notably, despite the nutrient load reduction policy adopted in the 1980s, the oxygen conditions of the Baltic Sea’s deep waters are still worsening. This study disentangles oxygen and hydrogen sulfide sources and sinks using the results from the 3-dimensional coupled MOM-ERGOM numerical model and investigates ventilation of the deep central Baltic Sea by the 29 biggest oxygen inflows from 1948 to 2018 utilizing the element tagging technic. Everywhere across the central Baltic Sea, except in the Bornholm Basin, a shift in oxygen consumption from sediments to water column and a significant positive trend in hydrogen sulfide content were observed. The most notable changes happened in the northern and western Gotland basins. Mineralization of organic matter, both in the water column and sediments, was identified as the primary driver of the observed changes. A significant negative trend in the lifetime of inflowing oxygen was found everywhere in the central Baltic Sea. It leads to the reduced efficiency of natural ventilation of the central Baltic Sea via the saltwater inflows, especially in the northern and western Gotland basins.

Genome sequencing in families with congenital limb malformations - Jonas Elsner; Martin A. Mensah; Manuel Holtgrewe; Jakob Hertzberg; Stefania Bigoni; Andreas Busche; Marie Coutelier; Deepthi C. de Silva; Nursel Elçioglu; Isabel Filges; Erica Gerkes; Katta M. Girisha; et al. (Human Genetics, 2021)
The extensive clinical and genetic heterogeneity of congenital limb malformation calls for comprehensive genome-wide analysis of genetic variation. Genome sequencing (GS) has the potential to identify all genetic variants. Here we aim to determine the diagnostic potential of GS as a comprehensive one-test-for-all strategy in a cohort of undiagnosed patients with congenital limb malformations. We collected 69 cases (64 trios, 1 duo, 5 singletons) with congenital limb malformations with no molecular diagnosis after standard clinical genetic testing and performed genome sequencing. We also developed a framework to identify potential noncoding pathogenic variants. We identified likely pathogenic/disease-associated variants in 12 cases (17.4%) including four in known disease genes, and one repeat expansion in HOXD13 . In three unrelated cases with ectrodactyly, we identified likely pathogenic variants in UBA2 , establishing it as a novel disease gene. In addition, we found two complex structural variants (3%). We also identified likely causative variants in three novel high confidence candidate genes. We were not able to identify any noncoding variants. GS is a powerful strategy to identify all types of genomic variants associated with congenital limb malformation, including repeat expansions and complex structural variants missed by standard diagnostic approaches. In this cohort, no causative noncoding SNVs could be identified.

The Indo‐European flyway: Opportunities and constraints reflected by Common Rosefinches breeding across Europe - Simeon Lisovski; Roland Neumann; Tomas Albrecht; Pavel Munclinger; Markus P. Ahola; Silke Bauer; Jaroslav Cepak; Thord Fransson; Sven Jakobsson; Tuomo Jaakkonen; Petr Klvana; Cecilia Kullberg; et al. (Journal of Biogeography, 2021)
Aim The configuration of the earth's landmasses influences global weather systems and spatiotemporal resource availability, thereby shaping biogeographical patterns and migratory routes of animals. Here, we aim to identify potential migratory barriers and corridors, as well as general migration strategies within the understudied Indo‐European flyway. Location Europe, Central Asia. Major taxon studied Common rosefinches. Methods We used a combination of theoretical optimization modelling and empirical tracking of Common Rosefinches ( Carpodacus erythrinus ) breeding across a large latitudinal gradient in Europe. First, we identified optimal migration routes driven by wind and resource availability along the Indo‐European flyway. Second, we tracked rosefinches from five breeding populations using light‐level geolocators. Finally, we compared to what extent empirical tracks overlapped with the modelled optimal routes. Results In autumn, theoretical wind driven migration routes formed a broad‐front corridor connecting Europe and the Indian Subcontinent while the theoretical resource driven routes formed a distinct north‐south divide. The latter pattern also reflected the rosefinch tracks with all but the most southerly breeding birds making a northern detour towards non‐breeding sites in Pakistan and India. In spring, the resource availability model predicted a similar migratory divide, however, the southern route seemed relatively more favourable and closely matched with the optimal wind driven migration routes. Spring tracking data showed larger overlap with the modelled wind driven migration routes compared to the resource driven routes. Main conclusions Optimal wind and resource driven migration routes along the Indo‐European flyway are seasonally specific and to a large extend do not overlap with one another. Under these conditions, migratory birds adopt seasonally distinct migration strategies following energy minimization strategy in autumn, driven by resource availability, and time minimizing strategy in spring, driven by wind conditions. Our optimal migration models can be applied worldwide and used to validate against empirical data to explain large‐scale biogeographic pattern of migratory animals.

Assessment of Uncertainties in Scenario Simulations of Biogeochemical Cycles in the Baltic Sea - H. E. Markus Meier; Moa Edman; Kari Eilola; Manja Placke; Thomas Neumann; Helén C. Andersson; Sandra-Esther Brunnabend; Christian Dieterich; Claudia Frauen; René Friedland; Matthias Gröger; Bo G. Gustafsson; et al. (Frontiers in Marine Science, 2019)

Assessment of Eutrophication Abatement Scenarios for the Baltic Sea by Multi-Model Ensemble Simulations - H. E. Markus Meier; Moa K. Edman; Kari J. Eilola; Manja Placke; Thomas Neumann; Helén C. Andersson; Sandra-Esther Brunnabend; Christian Dieterich; Claudia Frauen; René Friedland; Matthias Gröger; Bo G. Gustafsson; et al. (Frontiers in Marine Science, 2018)

Long-Term Mean Circulation of the Baltic Sea as Represented by Various Ocean Circulation Models - Manja Placke; H. E. Markus Meier; Ulf Gräwe; Thomas Neumann; Claudia Frauen; Ye Liu (Frontiers in Marine Science, 2018)

Patients’ Trust in Physician, Patient Enablement, and Health-Related Quality of Life During Colon Cancer Treatment - Nicole Ernstmann; Markus Wirtz; Anika Nitzsche; Sophie E. Gross; Lena Ansmann; Tristan D. Gloede; Julia Jung; Holger Pfaff; Walter Baumann; Stephan Schmitz; Melanie Neumann (Journal of Cancer Education, 2017)

Unterwasserabgabe nicht aus dem Grundablass — Motive und Folgen alternativer Ausleittiefen - Martin Schultze; Marieke Frassl; Michael Weber; Bertram Boehrer; Karsten Rinke; Ralf Sudbrack; Vincenz Neumann; Hartmut Willmitzer; Markus Möller; Wilfried Scharf (WASSERWIRTSCHAFT, 2016)

Kinetic modeling of riboflavin biosynthesis in Bacillus subtilis under production conditions - Markus Birkenmeier; Susanne Neumann; Thorsten Röder (Biotechnology Letters, 2014)

Echoes from the Past: A Healthy Baltic Sea Requires More Effort - Aarno T. Kotilainen; Laura Arppe; Slawomir Dobosz; Eystein Jansen; Karoline Kabel; Juha Karhu; Mia M. Kotilainen; Antoon Kuijpers; Bryan C. Lougheed; H. E. Markus Meier; Matthias Moros; Thomas Neumann; et al. (Ambio, 2014)

Forest floor vegetation response to nitrogen deposition in Europe - Thomas Dirnböck; Ulf Grandin; Markus Bernhardt‐Römermann; Burkhardt Beudert; Roberto Canullo; Martin Forsius; Maria‐Theresia Grabner; Maria Holmberg; Sirpa Kleemola; Lars Lundin; Michael Mirtl; Markus Neumann; et al. (Global Change Biology, 2014)
Chronic nitrogen (N) deposition is a threat to biodiversity that results from the eutrophication of ecosystems. We studied long‐term monitoring data from 28 forest sites with a total of 1,335 permanent forest floor vegetation plots from northern Fennoscandia to southern Italy to analyse temporal trends in vascular plant species cover and diversity. We found that the cover of plant species which prefer nutrient‐poor soils (oligotrophic species) decreased the more the measured N deposition exceeded the empirical critical load ( CL ) for eutrophication effects ( P = 0.002). Although species preferring nutrient‐rich sites (eutrophic species) did not experience a significantly increase in cover ( P = 0.440), in comparison to oligotrophic species they had a marginally higher proportion among new occurring species ( P = 0.091). The observed gradual replacement of oligotrophic species by eutrophic species as a response to N deposition seems to be a general pattern, as it was consistent on the European scale. Contrary to species cover changes, neither the decrease in species richness nor of homogeneity correlated with nitrogen CL exceedance (ExCL emp N). We assume that the lack of diversity changes resulted from the restricted time period of our observations. Although existing habitat‐specific empirical CL still hold some uncertainty, we exemplify that they are useful indicators for the sensitivity of forest floor vegetation to N deposition.

Combined effects of global climate change and regional ecosystem drivers on an exploited marine food web - Susa Niiranen; Johanna Yletyinen; Maciej T. Tomczak; Thorsten Blenckner; Olle Hjerne; Brian R. MacKenzie; Bärbel Müller‐Karulis; Thomas Neumann; H. E. Markus Meier (Global Change Biology, 2013)
Changes in climate, in combination with intensive exploitation of marine resources, have caused large‐scale reorganizations in many of the world's marine ecosystems during the past decades. The B altic S ea in N orthern E urope is one of the systems most affected. In addition to being exposed to persistent eutrophication, intensive fishing, and one of the world's fastest rates of warming in the last two decades of the 20th century, accelerated climate change including atmospheric warming and changes in precipitation is projected for this region during the 21st century. Here, we used a new multimodel approach to project how the interaction of climate, nutrient loads, and cod fishing may affect the future of the open C entral B altic S ea food web. Regionally downscaled global climate scenarios were, in combination with three nutrient load scenarios, used to drive an ensemble of three regional biogeochemical models ( BGM s). An Ecopath with Ecosim food web model was then forced with the BGM results from different nutrient‐climate scenarios in combination with two different cod fishing scenarios. The results showed that regional management is likely to play a major role in determining the future of the Baltic Sea ecosystem. By the end of the 21st century, for example, the combination of intensive cod fishing and high nutrient loads projected a strongly eutrophicated and sprat‐dominated ecosystem, whereas low cod fishing in combination with low nutrient loads resulted in a cod‐dominated ecosystem with eutrophication levels close to present. Also, nonlinearities were observed in the sensitivity of different trophic groups to nutrient loads or fishing depending on the combination of the two. Finally, many climate variables and species biomasses were projected to levels unseen in the past. Hence, the risk for ecological surprises needs to be addressed, particularly when the results are discussed in the ecosystem‐based management context.

Extremes of Temperature, Oxygen and Blooms in the Baltic Sea in a Changing Climate - Thomas Neumann; Kari Eilola; Bo Gustafsson; Bärbel Müller-Karulis; Ivan Kuznetsov; H. E. Markus Meier; Oleg P. Savchuk (Ambio, 2012)

Impact of Climate Change on Ecological Quality Indicators and Biogeochemical Fluxes in the Baltic Sea: A Multi-Model Ensemble Study - H. E. Markus Meier; Bärbel Müller-Karulis; Helén C. Andersson; Christian Dieterich; Kari Eilola; Bo G. Gustafsson; Anders Höglund; Robinson Hordoir; Ivan Kuznetsov; Thomas Neumann; Zohreh Ranjbar; Oleg P. Savchuk; et al. (Ambio, 2012)

Reconstructing the Development of Baltic Sea Eutrophication 1850–2006 - Bo G. Gustafsson; Frederik Schenk; Thorsten Blenckner; Kari Eilola; H. E. Markus Meier; Bärbel Müller-Karulis; Thomas Neumann; Tuija Ruoho-Airola; Oleg P. Savchuk; Eduardo Zorita (Ambio, 2012)

Age dependency of cerebral P-gp function measured with (R)-[11C]verapamil and PET - Martin Bauer; Rudolf Karch; Friederike Neumann; Aiman Abrahim; Claudia C. Wagner; Kurt Kletter; Markus Müller; Markus Zeitlinger; Oliver Langer (European Journal of Clinical Pharmacology, 2009)

Derivation of locally valid estimators of the aboveground biomass of Norway spruce - Markus Neumann; Robert Jandl (European Journal of Forest Research, 2005)

Adaptive divergence vs. environmental plasticity: tracing local genetic adaptation of metamorphosis traits in salamanders - Markus Weitere; Diethard Tautz; Dietrich Neumann; Sebastian Steinfartz (Molecular Ecology, 2004)
In order to assess the significance of local adaptation relative to environmental plasticity on the evolution of life history traits, we analysed the possible genetic basis of differences between pond‐ and stream‐breeding fire salamanders ( Salamandra salamandra ) in Germany. These salamanders typically deposit their larvae in small streams, where they grow until they are sufficiently large to metamorphose. However, some populations in Western Germany use ponds as larval habitat. Because habitat quality of streams differs from that of ponds one expects life history differences in the pond animals, which may result either from a plastic response or through genetic differentiation (i.e. local adaptation). Using a phylogeographical analysis of mitochondrial D‐loop sequences, we show that both stream and pond populations in Western Germany are derived from a single lineage that recolonized following the last glaciation. This finding suggests that pond breeding originated very recently. Our studies of habitat quality and metamorphic behaviour of larvae in natural ponds and streams disclosed that pond larvae experience a significantly reduced food supply and greater risk of drying than do stream larvae. Pond larvae metamorphose earlier at the cost of reduced mass. Common‐environment experiments with pond and stream larvae show that metamorphic behaviour of pond larvae under limited‐food conditions is determined genetically and is not simply a plastic response to the differing habitat conditions. These results show that phenotypic plasticity is less important than local adaptation in explaining differences in ecological diversification within this species and suggests the possibility of rapid evolution of genetic adaptations when new habitats are exploited.

Protein phosphatase activity is increased in a rat model of long-term β-adrenergic stimulation - Peter Bokník; Markus Fockenbrock; Stefan Herzig; Jörg Knapp; Bettina Linck; Hartmut Lüss; Frank Ulrich Müller; Thorsten Müller; Wilhelm Schmitz; Frank Schröder; Joachim Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

Phenylpropanoids in mycorrhizas of the Pinaceae - Markus Weiss; Jürgen Schmidt; Dieter Neumann; Victor Wray; Ruprecht Christ; Dieter Strack (Planta, 1999)